Health Protocol Intellectual Improvement During the COVID-19 Pandemic - Aim Matun Nadhiroh; Chlara Yunita Prabawati; Asta Adyani; Elisa Indah Verma (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2) or commonly known as COVID-19 has changed the social fabric of society. COVID-19 is spreading rapidly in more than 200 countries. Various regulations and policies have been made by the government to break the chain of transmission from COVID-19. However, not all people understand and obey because there is so much untrue information (hoax) circulating in the community. It is very important to educate the public, both in the city and in the village, about the importance of implementing the 5M health protocol (wearing masks, washing hands, maintaining distance, limiting mobility, and avoiding crowds), so that people can still carry out their activities outside the home, especially the breadwinners. The purpose of this activity is to increase the Intellectuality of Health Protocols during the COVID-19 Pandemic. The method of activity is given in the form of providing health education related to health protocols which are carried out door to door to reduce the risk of crowds. From the results of the community services the conclusion involve (1) The knowledge of the resident were improved which is known as local adherence (2) Residents want to apply health protocols when doing activities outside the home (3) The pandemic has created all to learn about the knowledge, motivation, self-esteem and believe encourage the level of enthusiasm of the societies accompany by the community’s services team that provides the resident facing the outbreak are no longer alone, we are aligned with the government to face it together. A determined strategy has to be improved to re-control the motivation and the behavior of the participant especially live in suburban and rural areas.